2021
DOI: 10.3233/faia210112
|View full text |Cite
|
Sign up to set email alerts
|

Application of CMSA to the Minimum Positive Influence Dominating Set Problem

Abstract: Construct, Merge, Solve & Adapt (CMSA) is a recently developed algorithm for solving combinatorial optimization problems. It combines heuristic elements, such as the probabilistic generation of solutions, with an exact solver that is iteratively applied to sub-instances of the tackled problem instance. In this paper, we present the application of CMSA to an NP-hard problem from the family of dominating set problems in undirected graphs. More specifically, the application in this paper concerns the minimum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…From the experiment results, it is demonstrated that CMSA can achieve similar performance compared to the exact solver for small to medium sized instances, while its performance is significantly better than the exact solver when it came to large instances. See [3,19,5,18] for recent research using CMSA.…”
Section: Hybrid Heuristicsmentioning
confidence: 99%
“…From the experiment results, it is demonstrated that CMSA can achieve similar performance compared to the exact solver for small to medium sized instances, while its performance is significantly better than the exact solver when it came to large instances. See [3,19,5,18] for recent research using CMSA.…”
Section: Hybrid Heuristicsmentioning
confidence: 99%
“…More recently, CMSA has been successfully applied in several instances and compared with other heuristics. In Akbay and Blum (2021), it is used to solve an NP-hard problem from the family of dominating set problems in undirected graphs, where the minimum positive influence dominating set problem is studied. The experiments show that CMSA outperforms the current state-of-the-art metaheuristics from the literature.…”
Section: Blum Et Al (2016) Presents a General Hybrid Metaheuristic Fo...mentioning
confidence: 99%
“…Unfortunately, such a high sensitivity to parameter values was noticed in some applications of CMSA in the literature. One of the examples concerns the preliminary application of CMSA to an NP-hard CO problem known as the minimum positive influence dominating set (MPIDS) problem [22]. Therefore, in this paper, we propose a self-adaptive variant of CMSA, called Adapt-CMSA, with the aim of obtaining an algorithm less sensitive to parameter values.…”
Section: Contributionmentioning
confidence: 99%
“…The first metaheuristic that was able to improve over [34] is the iterated carousel approach from [37]. Finally, the currently best metaheuristics are our own approaches: a negative learning ant colony optimisation approach from [38] and the preliminary standard CMSA approach from [22]. Both approaches perform on a comparable level.…”
Section: Application To the Mpids Problemmentioning
confidence: 99%
See 1 more Smart Citation